Product Innovation PT. FIF Group Uses 10 Types Of Innovation - Firnanda Dwi Yulianti; Aries Kurniawan (Cita konsultindo, 2023)
PT. FIF Group Gresik Branch is here to meet the needs of the community by facilitating financial planning that provides financing services for people who want to buy goods on credit and BPKB guaranteed multipurpose financing for business capital, marriage, home renovations etc. This study aims to determine the product innovation that is applied at PT. FIF GROUP in increasing motor vehicle financing. This study uses descriptive qualitative research in order to provide an in-depth picture. Data was taken through observation, direct interviews with consumers and PT. FIF Group at Jln RA. Kartini Building Kec. Kab. Gresik A document study was conducted to support this research. Product Innovation PT. FIF Group Uses 10 Types of Innovation In order to find customers more quickly and can understand the marketing strategies carried out by Marketing. The results of this study show an innovation where PT FIF GROUP only prepares a data base which is shared with marketing to offer loan funds via personal WhatsApp marketing. This marketing innovation can reduce labor and transportation costs. and the 10 Types of Innovation have proven successful in increasing revenue streams. Suggestions for the future so that the income stream can be even more increased.